The Use of Sikkam Bark as a Digestive Medicine in Perjuangan Village, Dairi Regency - Hana Lubis; Tara Nazwah (Indonesian Journal of Medical Anthropology, 2024)
This research discusses the use of Sikkam bark (Bischofia javanica Blume) as a digestive medicine in Perjuangan Village, Dairi Regency. Through a Health anthropology approach, this research explores local knowledge about the properties of Sikkam bark which is used to treat various digestive problems such as diarrhea, constipation and bloating. Data was collected through direct interviews and literature studies. The research results show that Sikkam bark is popular because of its availability, economical cost, and traditional belief in its efficacy. Its use involves certain processing processes and has side effects that need to be taken into account, such as stomach irritation and allergic reactions. People’s belief in the medical and magical benefits of Sikkam bark also influences the practice of using it. This research makes an important contribution to the preservation of traditional knowledge and strengthens scientific evidence regarding the benefits of Sikkam bark in traditional medicine Keywords: Traditional Medicine, digestion, beliefs